Scattering and Bound States of a Spin-1/2 Neutral Particle in the Cosmic String Spacetime - Fabiano M. Andrade; Cleverson Filgueiras; Edilberto O. Silva (Advances in High Energy Physics)
In this paper the relativistic quantum dynamics of a spin-1/2 neutral particle with a magnetic moment μ in the cosmic string spacetime is reexamined by applying the von Neumann theory of self-adjoint extensions. Contrary to previous studies where the interaction between the spin and the line of charge is neglected, here we consider its effects. This interaction gives rise to a point interaction: ∇·E=(2λ/α)δ(r)/r. Due to the presence of the Dirac delta function, by applying an appropriated boundary condition provided by the theory of self-adjoint extensions, irregular solutions for the Hamiltonian are allowed. We address the scattering problem obtaining the phase shift, S-matrix, and the scattering amplitude. The scattering amplitude obtained shows a dependency with energy which stems from the fact that the helicity is not conserved in this system. Examining the poles of the S-matrix we obtain an expression for the bound states. The presence of bound states for this system has not been discussed before in the literature.